Manajemen Pascaproduksi Pupuk NPK Phonska dalam Mendukung Efektivitas Distribusi di PT. Petrokimia Gresik - Jaisy Faris Putra Hendrawan; R. Achmad Djazuli; Resya Nurdyawati (CV.ITTC INDONESIA, 2026)
This study analyzes post-production management of NPK Phonska fertilizer at PT. Petrokimia Gresik using a qualitative case study approach. The research focused on the Warehouse and Bagging Department PH IV to examine the implementation of management functions, identification of operational constraints, and evaluation of system effectiveness. Findings reveal comprehensive implementation of four management functions—planning, organizing, directing, and controlling—within an integrated system covering packaging, quality control, storage, and distribution. Automated packaging technology achieved a throughput target of 300 bags per hour with ±0.5% weighing accuracy. The integrated quality control system improved product conformity from 97.8% to 99.2% and reduced customer complaints from 0.8% to 0.4%. Storage operations using a First-In-First-Out (FIFO) system with 304 buffer warehouses achieved 98.8% inventory accuracy and a 96.8% customer retention rate. Key constraints identified include machine downtime of 8–12%, skill gaps of 20–40% in core competencies, limited information system integration at 60–80%, and external challenges from demand variability and infrastructure limitations. Main recommendations include implementing predictive maintenance, strengthening HR development programs, comprehensive information system integration, and strategic partnership expansion to achieve sustainable competitive advantage in supporting national food security.